The Highest Stakes Poker Game Ever Played : Ronald Reagan, Mikhail Gorbachev, and the Reykjavik Summit of 1986 - Freeman, Stephanie (Vanderbilt University. Dept. of History, 2010)
History Department Honors Thesis, 2010. Awarded: High Honors. Winner of the 2010 Dewey Grantham Award for the best history honors thesis. Department of History College of Arts and Science